2017
DOI: 10.1038/bjc.2017.248
|View full text |Cite
|
Sign up to set email alerts
|

Choosing wisely: a model-based analysis evaluating the trade-offs in cancer benefit and diagnostic referrals among alternative HPV testing strategies in Norway

Abstract: Background:Forthcoming cervical cancer screening strategies involving human papillomavirus (HPV) testing for women not vaccinated against HPV infections may increase colposcopy referral rates. We quantified health and resource trade-offs associated with alternative HPV-based algorithms to inform decision-makers when choosing between candidate algorithms.Methods:We used a mathematical simulation model of HPV-induced cervical carcinogenesis in Norway. We compared the current cytology-based strategy to alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Evidence of deterioration in the predictive value of cytology as a primary screen in immunized women has been documented, although this does not translate into poor performance as a triage of HR‐HPV‐positive samples . It is also worth noting that the extent of triage in immunized populations will reduce given evidence from modeling studies that indicate 10‐year screening starting aged 30 is optimal . Conclusions from modeling endeavors, while extremely helpful, clearly incorporate various assumptions and differing levels of vaccine‐uptake, type of vaccine and dimensions of program (including the detail of catch‐up immunization) will exert influence.…”
Section: ±P16 ± Ki67mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of deterioration in the predictive value of cytology as a primary screen in immunized women has been documented, although this does not translate into poor performance as a triage of HR‐HPV‐positive samples . It is also worth noting that the extent of triage in immunized populations will reduce given evidence from modeling studies that indicate 10‐year screening starting aged 30 is optimal . Conclusions from modeling endeavors, while extremely helpful, clearly incorporate various assumptions and differing levels of vaccine‐uptake, type of vaccine and dimensions of program (including the detail of catch‐up immunization) will exert influence.…”
Section: ±P16 ± Ki67mentioning
confidence: 99%
“…83 It is also worth noting that the extent of triage in immunized populations will reduce given evidence from modeling studies that indicate 10-year screening starting aged 30 is optimal. 84,85 Conclusions from modeling endeavors, while extremely helpful, clearly incorporate various assumptions and differing levels of vaccine-uptake, type of vaccine and dimensions of program (including the detail of catch-up immunization) will exert influence. This makes a comprehensive, "one size fits all" solution difficult.…”
Section: Triage For Immunized Womenmentioning
confidence: 99%
“…For unvaccinated populations, primary HPV testing for these women may be considered resource intensive, potentially resulting in more colposcopies due to the higher prevalence of HPV in younger women [ 26 ]. However, a recent model-based analysis evaluating the health benefit and resource use trade-offs associated with primary HPV testing strategies for HPV-unvaccinated women concluded that primary HPV testing could start at an earlier age, e.g., at age 25 years, using a more conservative cytology-based triage algorithm for HPV-positive women to control colposcopy use [ 27 ]. An Australian study also suggested that primary HPV testing was preferred for unvaccinated women under 30 years of age, as well as for women in vaccinated cohorts [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary outcomes were re-test attendance, and re-test attendance within recommended timeframe, both recorded as dichotomous variables. Re-test was considered within the recommended time frame when was performed between month 12 and 18 after primary screening [17]. Women who returned up to 30 days off the range were also included.…”
Section: Methodsmentioning
confidence: 99%